2014
DOI: 10.3758/s13414-013-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding age-related reductions in visual working memory capacity: Examining the stages of change detection

Abstract: Visual working memory (VWM) capacity is reduced in older adults. Research has shown age-related impairments to VWM encoding, but aging is likely to affect multiple stages of VWM. In the present study, we recorded the event-related potentials (ERPs) of younger and older adults during VWM maintenance and retrieval. We measured encoding-stage processing with the P1 component, maintenance-stage processing with the contralateral delay activity (CDA), and retrieval-stage processing by comparing the activity for old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…However, the challenge may not simply be related to a reduced visual working memory storage capacity per se. Using behavioural and ERP methods to investigate the encoding, maintenance, and retrieval stages of a color change detection task, Ko et al (2014) found that older adults appeared to engage the same sensory encoding processes, and store the same number of objects during maintenance, as young adults. However, older adults retained stimuli at a lower resolution.…”
Section: Aging Effects On Visual Working Memorymentioning
confidence: 99%
“…However, the challenge may not simply be related to a reduced visual working memory storage capacity per se. Using behavioural and ERP methods to investigate the encoding, maintenance, and retrieval stages of a color change detection task, Ko et al (2014) found that older adults appeared to engage the same sensory encoding processes, and store the same number of objects during maintenance, as young adults. However, older adults retained stimuli at a lower resolution.…”
Section: Aging Effects On Visual Working Memorymentioning
confidence: 99%
“…Even normally aging older adults experience significant impairment in attentional tasks (Getzmann, Golob & Wascher, 2016; Sperduti, Makowski & Piolino, 2016), episodic memory (Manenti et al, 2016; Tromp et al, 2015) and working memory tasks (Jost et al, 2011; Ko et al, 2014), time perception (Turgeon, Lustig & Meck, 2016) and also speed of processing (Ball et al, 2013; Elgamal, Roy & Sharratt, 2011). If poorly prevented, these impairments might degrade the quality of life as well as the psychological well-being (Pusswald et al, 2015; Stogmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, other researchers using different paradigms have found similar positive activity with a comparable component (Begleiter, Porjesz and Wang, 1993) concerning working memory storage occurring over prefrontal and anterior areas in young adults (Ko et al, 2014). The sturdiness of this relationship leads us to utilize C250 as an index of storage in short-term memory that can be applied to other subject groups to study how short-term storage might vary with aging and cognitive conditions.…”
Section: Discussionmentioning
confidence: 56%
“…They attribute this effect to excessive attention to distracting information, which they supported with EEG spectral analysis of signals from frontal regions. Ko et al (2014) suggested that visual working memory capacity is reduced by aging, but the complexities of the entire memory storage, maintenance, and retrieval processes must be studied to unravel how this occurs. Also, Jost et al (2011) studied the contralateral delay activity of the EEG and determined that early in the retention interval older adults showed smaller filtering scores, which was indicative of retaining task-irrelevant information.…”
Section: Discussionmentioning
confidence: 99%